2018
DOI: 10.30802/aalas-cm-18-000049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rodent Thermoregulation on Animal Models in the Research Environment

Abstract: The thermal biology of laboratory mice encompasses a robust, dynamic, and multifaceted mixture of behavior and physiology. Physical and physiologic adaptations provide the remarkable capacity for mice to survive in temperatures as low as 4 °C and as high as 43 °C. 54,89 Comprehension of these complex systems necessitates a clear definition and solid understanding of the murine thermoneutral zone (TNZ), which is the range of temperatures across which the resting metabolic rate of heat production is at equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 117 publications
(156 reference statements)
3
80
0
Order By: Relevance
“…Relative to this problem, during pre-clinical research using murine models of cancer and graft versus host disease, our lab has clearly demonstrated that Institutional Animal Care and Use Committee (IACUC)-mandated mild cool housing temperature for laboratory mice (typically~22-23°C) is sufficient to cause chronic adrenergic stress 22 with activation of sympathetic nerves resulting in norepinephrine release needed for adaptive thermogenesis [23][24][25] . That this has a direct impact on the outcomes of studies involving a variety of disease models, including studies involving immune responses has been shown by comparing outcomes in mice housed under standard vs. thermoneutral temperatures [24][25][26][27] . Furthermore, our lab discovered that this chronic stress suppresses baseline anti-tumor immunity and accelerates tumor growth and metastasis 28,29 , while it also suppresses graft versus host disease following allogeneic hematopoietic stem cell transplantation 30,31 .…”
mentioning
confidence: 99%
“…Relative to this problem, during pre-clinical research using murine models of cancer and graft versus host disease, our lab has clearly demonstrated that Institutional Animal Care and Use Committee (IACUC)-mandated mild cool housing temperature for laboratory mice (typically~22-23°C) is sufficient to cause chronic adrenergic stress 22 with activation of sympathetic nerves resulting in norepinephrine release needed for adaptive thermogenesis [23][24][25] . That this has a direct impact on the outcomes of studies involving a variety of disease models, including studies involving immune responses has been shown by comparing outcomes in mice housed under standard vs. thermoneutral temperatures [24][25][26][27] . Furthermore, our lab discovered that this chronic stress suppresses baseline anti-tumor immunity and accelerates tumor growth and metastasis 28,29 , while it also suppresses graft versus host disease following allogeneic hematopoietic stem cell transplantation 30,31 .…”
mentioning
confidence: 99%
“…The studies presented here demonstrate that thermoneutral housing at 30°C resulted in improved survival as compared with standard housing at 22°C. Several recent reviews have described similar impact of thermoneutral housing on survival in other mouse models of human disease ( 12 , 15 , 22 , 23 ), including those used in metabolism, cancer, and infectious disease research. For instance, housing at thermoneutrality resulted in slower tumor growth and reduced metastasis in mouse cancer models compared with housing at standard temperatures, due to enhanced antitumor immune responses ( 23 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the housing temperature of mice influences experimental phenotypes ( 13 ), model development ( 12 ), and translation of study results ( 12 15 ). In particular, temperature-related alteration of immune responses has direct effects on mouse models of cancer ( 16 ), graft-versus-host-disease ( 17 ), LPS-induced inflammation ( 18 , 19 ), and infectious disease ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…at 26°C [15]. Importantly, recent guidelines for preclinical studies in sepsis research [32,33] and cerebrovascular research [34][35][36], with the emphasis to improve reproducibility and translational impact, neglected the impact of ambient temperature on pathogenesis of inflammatory diseases or did not consider that their recommended lower baseline limit for housing temperatures of small rodents causes chronic 'cold' stress [37,38]. Furthermore, ignoring the role of ambient temperature on basal physiological responsiveness in small animals frequently used in preclinical sepsis models leads to far-reaching repercussions of profound misinterpretation: Time course of body temperature lowering and development of hypothermia is used for prognosis prediction while mice are under chronic cold stress for mice [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%